2016
DOI: 10.9767/bcrec.12.1.605.24-31
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Novel Integrated Dielectric Barrier Discharge Plasma as Ozone Generator

Abstract: <p>This paper presents a characterization of an integrated ozone generator constructed by seven of reactors of Dielectric Barrier Discharge Plasma (DBDP). DBDP a has spiral-cylindrical configuration. Silence plasma produced ozone inside the DBDP reactor was generated by AC-HV with voltage up to 25 kV and maximum frequency of 23 kHz. As a source of ozone, dry air was pumped into the generator and controlled by valves system and a flowmeter. We found ozone concentration increased with the applied voltage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 17 publications
0
9
0
3
Order By: Relevance
“…shelf 1, 2, 3, and freezing compartment for 30 minutes every day.Ozone concentration applicatedinside of fish storage system by ozone technology in refrigerator ( Fig.1) can be determinated. The concentration of ozone in the refrigerator is the ozone concentration generated by the generator multiplied by the flowrate and divided by the volume of the refrigerator [14]. In this study we used ozone concentraion inside refrigerator was 6 mg/L.…”
Section: Methods 21 Ozone Generation With Dbd Plasma Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…shelf 1, 2, 3, and freezing compartment for 30 minutes every day.Ozone concentration applicatedinside of fish storage system by ozone technology in refrigerator ( Fig.1) can be determinated. The concentration of ozone in the refrigerator is the ozone concentration generated by the generator multiplied by the flowrate and divided by the volume of the refrigerator [14]. In this study we used ozone concentraion inside refrigerator was 6 mg/L.…”
Section: Methods 21 Ozone Generation With Dbd Plasma Systemmentioning
confidence: 99%
“…Previous research has been done on the red tilapia, which represents white-fleshed fish, in the refrigerator where ozone was delivered with a concentration of 0.5-45 ppm. The TVBN test results showed that fish on each shelf in the refrigerator with ozone treatment still meet Indonesian NationalStandard (INS) [14,15], until the 16th day. In contrast, fish placed on refrigerators with no ozone treatment have an untoleratedtvbn value on the 8th day.…”
mentioning
confidence: 99%
“…From the calculation on equation 1- (4), it can be determined that the ignition coil amplifying factor is 196.71. This result is then used to determine output voltage on the coil's secondary windings.…”
Section: A Capacitive Discharge Ignition Circuitmentioning
confidence: 99%
“…Although ozone can be produced naturally, it can be generated artificially through various ozonizer methods for the industrial purpose such as corona discharge/dielectric barrier discharge, UV-based ionization, and electrolysis [2]- [6]. Corona discharge or dielectric barrier discharge method is more costeffective than other methods [2]- [4]. The air ionization process is started when oxygen molecules give and get electrons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation